2012
DOI: 10.1021/ct200680g
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Opening and Closing of Hsp70 Chaperones by Coarse-Grained Molecular Dynamics

Abstract: Heat-shock proteins 70 (Hsp70s) are key molecular chaperones which assist in the folding and refolding/disaggregation of proteins. Hsp70s, which consist of a nucleotide-binding domain (NBD, consisting of NBD-I and NBD-II subdomains) and a substrate-binding domain [SBD, further split into the β-sheet (SBD-β) and α-helical (SBD-α) subdomains], occur in two major conformations having (a) a closed SBD, in which the SBD and NBD domains do not interact, (b) an open SBD, in which SBD-α interacts with NBD-I and SBD-β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 43 publications
3
44
1
Order By: Relevance
“…Single-molecule FRET experiments (22) showed that the open SBD form is present (8-11%) under ADP conditions, supporting our results. A weak interaction between the α/β-folded subdomains and physical separation of subdomains was also observed in native-state molecular simulations by using the replica exchange method or following the dynamics of DnaK over tens of nanoseconds of equilibrium molecular dynamics (23,24). As pointed out above, the subdomain interface is easily perturbed allowing the opening of the lid, whereas β7-β8 are still attached to the β-core, which reduces energy costs.…”
Section: Discussion Bifurcating Unfolding Pathways For Sbd and Mechanmentioning
confidence: 68%
“…Single-molecule FRET experiments (22) showed that the open SBD form is present (8-11%) under ADP conditions, supporting our results. A weak interaction between the α/β-folded subdomains and physical separation of subdomains was also observed in native-state molecular simulations by using the replica exchange method or following the dynamics of DnaK over tens of nanoseconds of equilibrium molecular dynamics (23,24). As pointed out above, the subdomain interface is easily perturbed allowing the opening of the lid, whereas β7-β8 are still attached to the β-core, which reduces energy costs.…”
Section: Discussion Bifurcating Unfolding Pathways For Sbd and Mechanmentioning
confidence: 68%
“…In the case of the barnase-barstar, self-assembled structures were closely resembling the known target complex (Basdevant, Borgis, & Ha-Duong, 2013). Finally, the UNRES force field (Liwo, Czaplewski, Pillardy, & Scheraga, 2001), originally developed to simulate folding and aggregation of small proteins (Czaplewski, Kalinowski, Liwo, & Scheraga, 2009), has been recently used to study the recognition process of Hsp70 chaperones (Gołaś et al, 2012), and the aggregation of the β-amyloid fragments (Aβ 1-28 ), demonstrating that helical intermediate secondary structure elements may play a role during aggregation (Rojas, Liwo, & Scheraga, 2011).…”
Section: Tackling Protein-protein Interactions At Coarse-grained Resomentioning
confidence: 94%
“…3 The SBD-closed (ADP-bound) structure of the DnaK Hsp70 chaperone from E. coli was determined by Zuiderweg and coworkers 10 by NMR spectroscopy (PDB: 2KHO). Recently, 11 we carried out molecular dynamics simulations, using the coarse-grained UNRES force field 12-15 developed in our laboratory, of the conformational transition of DnaK, starting from the SBD-closed 2KHO structure. We determined a probable structure of the SBD-open conformation 11 , which was unknown at the time, and which turned out to be very close to the x-ray structure of the SBD-open (ATP-bound) form of DnaK, which was determined by Mayer and coworkers 3 after the results of our simulations had been published.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 11 we carried out molecular dynamics simulations, using the coarse-grained UNRES force field 12-15 developed in our laboratory, of the conformational transition of DnaK, starting from the SBD-closed 2KHO structure. We determined a probable structure of the SBD-open conformation 11 , which was unknown at the time, and which turned out to be very close to the x-ray structure of the SBD-open (ATP-bound) form of DnaK, which was determined by Mayer and coworkers 3 after the results of our simulations had been published. Starting from a homology model of the SBD-open conformation of bovine Hsp70, and using all-atom molecular dynamics with the GROMOS force field, Senet, Ripoll, and coworkers 16 simulated the initial stage of the dissociation of SBD-β from the NBD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation